2013
DOI: 10.1159/000356969
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminal Agrin Fragment - A New Fast Biomarker for Kidney Function in Renal Transplant Recipients

Abstract: Background: The C-terminal agrin fragment (CAF) is a cleavage product of agrin, the major proteoglycan of the glomerular basement membrane. This article studies if CAF could serve as a biomarker for renal function in renal transplant recipients. Material and Methods: We measured serum CAF and creatinine concentrations and calculated estimated glomerular filtration rate (eGFR) (MDRD) in 96 healthy individuals and in 110 end-stage renal disease patients undergoing kidney transplantation before and after transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 70 publications
(39 reference statements)
0
25
1
Order By: Relevance
“…Indeed, agrin is expressed in the kidney and CAF22 has been related to the damage of the glomerular basement membrane 37, 38. In our study patients with renal failure as well as with dialysis were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, agrin is expressed in the kidney and CAF22 has been related to the damage of the glomerular basement membrane 37, 38. In our study patients with renal failure as well as with dialysis were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent cross-over study comparing high-flow CCPD and standard CAPD did not observe any significant differences in peritoneal substrate clearances for molecules up to a mass of beta 2 -microglobuline (11.8 kDa, [13]). Recently we showed that serum levels of total C-terminal agrin fragment (tCAF), a 22 k-Da protein derived from agrin, correlated with kidney function in renal transplant and CCPD patients [14,15]. The finding in the latter study was primarily due to the low contribution of peritoneal clearance to the total clearance of tCAF.…”
Section: Introductionmentioning
confidence: 92%
“…The COOH terminus V domain of perlecan is similar to another HS proteoglycan, agrin, which is the major proteoglycan of the glomerular basement membrane. The COOH-terminal agrin fragment is a known marker of neuronal muscular remodeling, but it has recently been shown to be a potential biomarker for renal function in renal transplant recipients (322). Like other mentioned angiogenesis inhibitors, such as arresten, canstatin, endostatin, and tumstatin, endorepellin mediates its antiangiogenesis functions through binding to ␣2␤1-integrin, a key angiogenesis receptor (376).…”
Section: Posttranslationally Modified Proteins Affect Cell Phenotype:mentioning
confidence: 99%